SERS analysis of selectively captured exosomes using an integrin‐specific peptide ligand. (29th August 2017) - Lee, Changwon; Carney, Randy; Lam, Kit; Chan, James W.
Abstract: We demonstrate selective capturing of exosomes for surface‐enhanced Raman spectroscopy (SERS) analysis using a thiolated peptide ligand that is bound to the surface of silver nanoparticles via thiol‐metallic bond formation. The ligand preferentially binds to α3ß1 integrin over‐expressed in exosomes secreted from SKOV‐3 cancer cells. Several Raman peaks at 894 cm −1, 1, 080 cm −1, 1, 252 cm −1, 1, 340 cm −1, and 1, 380 cm −1 specific to SKOV‐3 exosomes are detected above the background signals generated from the nanoparticle and the ligand. In comparison, α3ß1 integrin negative exosomes secreted from Jurkat cells showed no detectable exosome specific SERS signal, confirming the high specificity of this ligand‐based SERS detection approach. This study shows the potential of developing a target‐specific SERS detection approach for characterizing exosomes from a heterogeneous mixture in body fluid for early‐stage disease diagnostics. Abstract : Using thiolated peptide ligands bound to the surface of silver nanoparticles, we demonstrate selective capturing and SERS analysis of exosomes. The ligand preferentially binds to α3ß1 integrin overexpressed in exosomes secreted from SKOV‐3 cancer cells. Raman peaks at 894 cm −1, 1, 080 cm −1, 1, 252 cm −1, 1, 340 cm −1, and 1, 380 cm −1 specific to SKOV‐3 exosomes are detected.